Eco-physiological response to water stress of drought-tolerant and drought-sensitive tomato genotypes. (3rd July 2016) - Rigano, M. M.; Arena, C.; Di Matteo, A.; Sellitto, S.; Frusciante, L.; Barone, A.
Abstract : Water stress is an increasing environmental constraint affecting tomato growth and yield in Mediterranean areas. Solanum pennellii is a wild tomato species that exhibits a higher water use efficiency compared with cultivated S. lycopersicum . In particular, a cultivated line carrying a small S. pennellii region on chromosome 9 (IL 9-2-5) was identified as more tolerant to water deficit. In this work, the tolerant (IL 9-2-5) and the susceptible (M82) genotypes were subjected to three different water regimes: irrigation with 100% (V1), 50% (V2) and 25% (V3) field capacity. To evaluate the physiological response of IL 9-2-5 and M82 to water deficit, leaf functional traits, plant biomass production and maximal PSII photochemical efficiency were measured together with photosynthetic pigments and phenolic compounds. The higher tolerance to water deficiency of IL 9-2-5 was associated with the development of a better antioxidant system, especially in treatment V3. In addition, IL 9-2-5 had higher values of sclerophylly and leaf dry matter content thus confirming that the tolerance of IL 9-2-5 can be attributed to traits related to leaf morphology and physiology. In future, identification of polymorphisms in key-genes controlling these traits can guide breeding efforts aimed at improving susceptible genotypes.